Sistem Informasi Berbasis Mobile Benda-Benda Tradisional Pada Museum Balanga Palangkaraya - Muhammad Haris Qamaruzzaman; Teguh Prasetya; Shamil Anggi Islamova H (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
In this era of globalization, the process of information dissemination through various media can be one with the internet, because the internet is an information technology provider means any time used by the community at the moment and extend the spread of the information Balanga City Museum collection of PalangkaRaya. This research aims at the development of mobile-based information system as the solution of data processing or storage, both in terms of reporting which can help as a media information service for people who need information Introduction to historical heritage objects (Ethnography) of Dayak Culture that exists in the Museum Balanga palangkaraya become more effective and efficient as well as being a solution for systems that are running currently, in conducting promotional activities are still using media promotion through books, brochures, leaflets or in the form of an ad in the newspaper that felt too much of the costs incurred for promotional activities. The design of the system for the flow of functional systems that are running or built using UML as well as for the look of the interface using Balsamiq Mockups. System development is done using the waterfall as one method to construct the system quickly. Implementation of applications using mobile testing conducted using black-box, and the results match expectations between systems that are built and thoroughly tested.